Marketing Strategy Analysis using Strength Opportunity Aspiration Result (SOAR) Strategy and Quantitative Strategic Planning Matrix (QSPM) at PT. XYZ - Firmansyah, Muhammad Daffa Dzaky; Iriani, Iriani (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The intense competition involving many business actors demands that these entrepreneurs be able to adapt to the evolving business conditions. In facing this competition, running a business requires a well-thought-out strategy to help business owners anticipate the impact of such events and remain competitive. The SOAR Analysis is an approach consisting of Strengths, Opportunities, Aspirations, and Results components derived from the Appreciative Inquiry (AI) approach, where planning focuses on existing strengths and available opportunities. The Quantitative Strategic Planning Matrix (QSPM) is applied to prioritize various factors influencing strategic planning. The objective of QSPM analysis is to determine the best strategies to be implemented. The QSPM matrix can identify the strategies to be used in the decision-making stage, which can later be applied to the company. From the results of the QSPM matrix, strategy 1 obtained the highest TAS value of 2.39, while strategy 2 had the lowest TAS value of 0.86, indicating that strategy 1 is the top priority that the company can implement.